Explanatory Practice in Family Studies - Sprey, Jetse (1995)
The article makes a case for a more flexible and realistic explanatory practice in the family field. The conventional linkage between the worth of an explanatory statement and its predictive power, for, example, reflects cultural assumptions as much as it does rational thought. In one's culture, knowledge implies power so that prediction allows for control of the present and the foreseeable future. The sense making of, any specific descriptive piece of work depends on its focus. For example, how well does it allow noise to be separated from relevant information? How, far do its data reach into the future? To give a mundane example, a telephone directory provides reliable. information and a degree of predictive power but does not offer, valid grounds for conceptual, let alone theoretical, reasoning